2014
DOI: 10.1128/aac.00021-14
|View full text |Cite
|
Sign up to set email alerts
|

Kibdelomycin Is a Potent and Selective Agent against Toxigenic Clostridium difficile

Abstract: dClostridium difficile is the causative agent of C. difficile-associated diarrhea (CDAD), with increased risk in elderly populations. Kibdelomycin, a novel natural-product inhibitor of type II topoisomerase enzymes, was evaluated for activity against C. difficile and gastrointestinal anaerobic organisms. Toxigenic C. difficile isolates (n ‫؍‬ 168) from U.S. hospitals and anaerobic Gram-positive and Gram-negative organisms (n ‫؍‬ 598) from Chicago-area hospitals were tested. Kibdelomycin showed potent activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…It binds the GyrB and ParE enzymes in a unique U-shaped binding mode with multipoint contacts (12). Kibdelomycin selectively inhibited C. difficile without affecting many other anaerobic gut bacteria, including Bacteroides species (11). It shows potent bactericidal activity against S. aureus, although it is slower than fluoroquinolones (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It binds the GyrB and ParE enzymes in a unique U-shaped binding mode with multipoint contacts (12). Kibdelomycin selectively inhibited C. difficile without affecting many other anaerobic gut bacteria, including Bacteroides species (11). It shows potent bactericidal activity against S. aureus, although it is slower than fluoroquinolones (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Kibdelomycin A is a less potent inhibitor of S. aureus gyrase supercoiling (IC 50 , 400 nM) and topoisomerase IV catenation (ParE IC 50 , 5,000 nM) but has been shown to be a potent inhibitor of E. coli gyrase B ATPase activity (IC 50 , 9 nM) though a poor inhibitor of the E. coli ParE ATPase (IC 50 , 6,400 nM) (10). We reported that kibdelomycin is a selective and potent inhibitor of Clostridium difficile growth without significantly affecting anaerobic Gram-negative bacteria, including Bacteroides species (11). It showed potent in vivo activity against C. difficile infection without systemic exposure (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The co-crystal structures of kibdelomycin bound to the N-terminal domains of S. aureus GyrB and ParE revealed a novel mode of ‘dual’ ATPase inhibition by blocking ATP binding and destabilizing GyrB/ParE subunit dimerization 77 . Kibdelomycin displays strong antimicrobial activities against predominantly Gram-positive bacteria, including MRSA and C. difficile 78 , 79 . The MIC 90 for C. difficile was 0.5 mg/L, similar to the novel therapeutic fidaxomicin, but more potent than metronidazole and vancomycin 78 .…”
Section: Challenges In Developing Novel Antimicrobials Targeting Replmentioning
confidence: 99%
“…Encouraging results were obtained with it in a hamster model of CDI in terms of survival (80–100%), bacterial elimination (2- to 5-log reduction of C. difficile counts) and a practically absent enteral absorption [25]. Upcoming phase I human trials have not yet been announced.…”
Section: Antibiotics and Non-antibiotic Anticlostridial Agentsmentioning
confidence: 99%